Countermeasures for Preventing and Treating Opioid Overdose. Issue 3 (29th November 2020) - France, Charles P.; Ahern, Gerard P.; Averick, Saadyah; Disney, Alex; Enright, Heather A.; Esmaeli‐Azad, Babak; Federico, Arianna; Gerak, Lisa R.; Husbands, Stephen M.; Kolber, Benedict; Lau, Edmond Y.; Lao, Victoria; et al.
Abstract : The only medication available currently to prevent and treat opioid overdose (naloxone) was approved by the US Food and Drug Administration (FDA) nearly 50 years ago. Because of its pharmacokinetic and pharmacodynamic properties, naloxone has limited utility under some conditions and would not be effective to counteract mass casualties involving large‐scale deployment of weaponized synthetic opioids. To address shortcomings of current medical countermeasures for opioid toxicity, a trans‐agency scientific meeting was convened by the US National Institute of Allergy and Infectious Diseases/National Institutes of Health (NIAID/NIH) on August 6 and 7, 2019, to explore emerging alternative approaches for treating opioid overdose in the event of weaponization of synthetic opioids. The meeting was initiated by the Chemical Countermeasures Research Program (CCRP), was organized by NIAID, and was a collaboration with the National Institute on Drug Abuse/NIH (NIDA/NIH), the FDA, the Defense Threat Reduction Agency (DTRA), and the Biomedical Advanced Research and Development Authority (BARDA). This paper provides an overview of several presentations at that meeting that discussed emerging new approaches for treating opioid overdose, including the following: (1) intranasal nalmefene, a competitive, reversible opioid receptor antagonist with a longer duration of action than naloxone; (2) methocinnamox, a novel opioid receptor antagonist; (3) covalent naloxone nanoparticles; (4) serotonin (5‐HT)1A receptor agonists; (5) fentanyl‐binding cyclodextrin scaffolds; (6) detoxifying biomimetic "nanosponge" decoy receptors; and (7) antibody‐based strategies. These approaches could also be applied to treat opioid use disorder.